2011
DOI: 10.4137/cmrh.s6598
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole versus Clomiphene Citrate for Induction of Ovulation in Patients with Polycystic Ovarian Syndrome Undergoing Intrauterine Insemination

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is one of the most common endocrinopathies affecting women in the reproductive age group, and is one of the most common causes of hyperandrogenic anovulatory infertility. The aromatase inhibitor, letrozole, has been used for induction of ovulation. The purpose of this study was to compare the effects of letrozole and clomiphene citrate in induction of ovulation among patients with PCOS undergoing intrauterine insemination.MethodsIn a double-blind randomized study, 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…In the three studies with low risk of allocation concealment bias, the comparison between CC and letrozole showed lower EMT in the CC group (WMD, −1.68; 95% CI, −3.27 to −0.08; I 2 = 98%). However, including studies with low risk of randomization bias, performance bias and detection bias showed a similar effect estimate but without statistical significance, which could be due to low power of the studies.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In the three studies with low risk of allocation concealment bias, the comparison between CC and letrozole showed lower EMT in the CC group (WMD, −1.68; 95% CI, −3.27 to −0.08; I 2 = 98%). However, including studies with low risk of randomization bias, performance bias and detection bias showed a similar effect estimate but without statistical significance, which could be due to low power of the studies.…”
Section: Resultsmentioning
confidence: 89%
“…Pooled analysis of 15 studies showed EMT to be lower (WMD, −1.39; 95% CI, −2.27 to −0.51; I 2 = 100%) with a lower pregnancy rate (RR, 0.78; 95% CI, 0.63–0.95; I 2 = 43%) in the CC group than in the letrozole group (Figures and ). Ovulation rates were comparable between the groups (13 trials, RR, 0.97; 95% CI, 0.90–1.04; I 2 = 47%; Figure ). Data of EMT per woman were available in eight studies; pooled analysis showed EMT to be lower in the CC group (WMD, −2.10; 95% CI, −3.22 to −0.98; I 2 = 96%).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations